The Influence of Economic Value Added, Good Corporate Governance and Business Risk on Stock Returns Through Firm Value - Setyawati, Irma; Nugroho, M Yusuf (Graduate Program Magister Manajemen Pendidikan, 2023)
The purpose of this study is to analyze and obtain empirical evidence on the influence of Economic Value Added (EVA), Good Corporate Governance (GCG), and business risk on stock returns through firm value in a case study of companies listed in the LQ45 index. The research was conducted on 22 companies using purposive sampling method to select samples for the period from 2018 to 2022. The data analysis method used was panel data regression using Structural Equation Modeling (SEM) in Stata 14.2 software application. The results of this study indicate that Economic Value Added (EVA) has a positive but not significant effect on stock returns, Good Corporate Governance (GCG) has a positive but not significant effect on stock returns, business risk has a positive and significant effect on stock returns, and firm value has a positive and significant effect on stock returns. Economic Value Added (EVA) has a positive but not significant effect on firm value, Good Corporate Governance (GCG) has a positive and significant effect on firm value, and business risk has a negative but not significant effect on firm value. Economic Value Added (EVA) has a positive but not significant effect on stock returns through firm value, Good Corporate Governance (GCG) has a positive and significant effect on stock returns through firm value, and business risk has a negative but not significant effect on stock returns through firm value.